The most productive and disease resistable peach varieties for the wet subtropics in Sochi - N. E. Smagin; J. S. Abilfazova (Новые технологии, 2017)
A pomogological description and characteristics of the most productive Persica vulgaris (Mill.) varieties with good quality fruits in the subtropical zone of Sochi - Medin red, Early blow, Summerset, Comanche, Redhaven are given. These varieties have a reduced demand for cold in winter and heat in spring during peach blossoming, the main limiting factor for its cultivating in the humid subtropics of Sochi.